2009
DOI: 10.1017/s0025315409991391
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and histopathological effects of Monstrilla sp. (Copepoda: Monstrilloida) and other parasites in the brown mussel Perna perna from Brazil

Abstract: During a parasitological survey of the brown mussel Perna perna from highly productive culture fields in the southern sector of Brazil, monstrilloid copepods were discovered in the mantle of this mytilid bivalve. Numerous specimens of endoparasitic copepods were found within nodules in the mantle of the host; they belong to an undetermined species of Monstrilla. Monstrilloid copepods were known to be endoparasitic in polychaetes and in one species of prosobranch mollusc only; their occurrence as parasites of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…However, most copepods which use marine bivalves as hosts inhabit the pallial cavity and their body is modified to attach the gills (Kim & Sato, 2010). In Brazil, Da Suárez- Morales et al (2010) reported Monstrilla in the brown mussel Perna perna. By other hand, Ostrincola patagonianus and another, unidentified, but closely related to Tisbe celata copepod, both inhabiting the pallial cavity of Mytilus sp., are known from South America (Humes, 1988;unpubl.…”
Section: Estudio Histopatológico Del Chorito Mytilus Chilensis (Mytilmentioning
confidence: 99%
“…However, most copepods which use marine bivalves as hosts inhabit the pallial cavity and their body is modified to attach the gills (Kim & Sato, 2010). In Brazil, Da Suárez- Morales et al (2010) reported Monstrilla in the brown mussel Perna perna. By other hand, Ostrincola patagonianus and another, unidentified, but closely related to Tisbe celata copepod, both inhabiting the pallial cavity of Mytilus sp., are known from South America (Humes, 1988;unpubl.…”
Section: Estudio Histopatológico Del Chorito Mytilus Chilensis (Mytilmentioning
confidence: 99%
“…Monstrilloids are protelean parasites of benthic polychaetes and molluscs; most postnaupliar and preadult stages are endoparasitic (Suárez-Morales 2011;Suárez-Morales et al 2010. Only the first naupliar stage, a final, transitory copepodid stage ("subimago"), and the planktonic adults are free-living.…”
Section: Introductionmentioning
confidence: 99%
“…The nauplii and most copepodid stages of monstrilloid copepods are endoparasites of polychaete worms and prosobranch and bivalve molluscs (Boxshall & Halsey 2004;Suárez-Morales et al 2010, 2013b, but very little is known of their host specificity. The availability of suitable host species for the infective stages is obviously critical to determining the distribution of the free-living adults, but until we have a better understanding of the identity of host species we can only speculate on the factors determining species distributions.…”
Section: Discussionmentioning
confidence: 99%